PERSEPSI ANGGOTA BADAN PERWAKILAN DESA TERHADAP ORGANISASI PEKA GENDER DI KABUPATEN SLEMAN - L. Andriani Purwastuti (LPPM UNY, 2006)
This research aims to know the perception of members of Badan Perwakilan Desa (Board of Village Representative) on the gender equity and gender awareness-based organization. The populations in this research are 1.118 members of BPD in Sleman. Random sampling is used to determine the sample. The samples gained are villages 10 out of 80 villages in Sleman Regency. This determination based on Jacob Cohen’s formula results in 108 people as the sample. Data collection uses the descriptive-qualitative technique and presentation. The research result shows that the perception of members of BPD on gender equity is considered good. It is proven by 8.1 mean from 11 (73,64%) total value. Their perception on gender awareness-based organization tends to be good. It is shown by 25.3 mean from 33 (76,67%) total value. However, taking into account items, some indicators on the gender equity seems mislead. Some members of BPD still consider that female cannot work using physics (53,8%). They do not want their sons get lower level of education than their daughters (54,9%). Some of them still view that leader is better to men than to women (33%). Receptionist is better to women (35,2%). Some of the members think that they do not need children’s playground in the office (45,1%).